Whiteface Improv Comedy and Anti-Blackness - Büch, Michel (American Frictions, 2022)
This study originates in the observation that improv comedy or improvised theater has such a vast majority of white people practicing it, while other improvisational or comedic art forms (jazz, freestyle rap, stand up) are historically grounded in and marked as Black cultural production. What it is about improv that makes it such a white space? Can an absence be an object of study? If so, what is there to study? Where should one look?